Pengelolaan Wakaf Produktif di Lembaga Amil Zakat Nurul Fikri Sampit Ditinjau dari Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf - Hasan, Sudirman; Sari, Erna (Badan Wakaf Indonesia, 2021)
Abstract: Lembaga Amil Zakat Nurul Fikri as the object of research for various reasons underlying this paper, including the policy of zakat institutions to receive waqf. Basically, the authority of zakat institutions is only to receive zakat infaq and shadaqah, but it is different from Nurul Fikri who also receives and manages waqf. Among them productive waqf that is being managed is productive sengon tree whose initial allocation of waqf is to build educational institutions. In this article, it contains about how the legality of waqf institution law has authority as nadzir waqf and how to manage and develop productive waqf if reviewed from Law No. 41 of 2004. This type of research is empirical or field research that uses description analysis with qualitative approach. The results showed that 1) Zakat Nurul Fikri Institution receives authority as nadzir waqf because of the encouragement of social factors of the community to make some of its assets, in addition this Institution also makes a program of the establishment of an independent waqf institution and the plan is a program that will be established in 2021. 2). In developing and managing productive waqf Nurul Fikri has followed in accordance with what is intended by law No. 41 of 2004, but there are several things that need to be improved related to institutional problems. Keywords: productive waqf, management, nadzir